Utilization of UPLC-tandem mass spectrometry for quantitation of colouring matters in dietary formulation - Zaghary, Wafaa Abdou; Abdalla, Ahmed Mostafa; Hanna, Emily Tawfik; Zanoun, Marwa Abdel Rahman Tohamy (European Journal of Chemistry, 2019)
A simple and sensitive ultra-performance liquid chromatography with Tandem Mass Spectrometric detection (UPLC-MS/MS) method was developed and validated for the simultaneous quantitation of two food colouring matters, Curcumin (CUR) and Riboflavin (RIB). Chromatographic separation was done on Hypersil gold 50×2.1 mm (1.9 μm) column, with gradient programing of mobile phase starting with aqueous 0.1% formic acid and increasing the percentage of 0.1% formic acid in acetonitrile. The utilization of multiple reaction monitoring (MRM) improved the selectivity of detection and decreased the matrix effect. The method was linear in the range of 5-500 ng/mL for CUR and RIB. Intra- and inter-day reproducibility were within the accepted criteria. The method was successfully applied for the determination the laboratory prepared mixtures of the two selected colouring matters. The use of mass spectrometry enhanced the selectivity and sensitivity of detection which allows the robust use of the method in routine quality control tests of the two colouring matters (CUR and RIB).